2020
DOI: 10.1093/mnras/staa175
|View full text |Cite
|
Sign up to set email alerts
|

A large, deep 3 deg2 survey of H α, [O iii], and [O ii] emitters from LAGER: constraining luminosity functions

Abstract: We present our measurements of the Hα, [Oiii], and [Oii] luminosity functions as part of the Lyman Alpha Galaxies at Epoch of Reionization (LAGER) survey using our samples of 1577 z = 0.47 Hα-, 3933 z = 0.93 [Oiii]-, and 5367 z = 1.59 [Oii]selected emission line galaxies in a 3 deg 2 single, CTIO/Blanco DECam pointing of the COSMOS field. Our observations reach 5σ depths of 8.2 × 10 −18 erg s −1 cm −2 and comoving volumes of (1 − 7) × 10 5 Mpc 3 making our survey one of the deepest narrowband surveys. We selec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 116 publications
(268 reference statements)
1
34
0
Order By: Relevance
“…Hereafter, when referring to HAEs or O3Es, we also imply that each species lies in these redshift bounds, and that [OIII] refers to [OIII]λ5007 unless otherwise stated. Our 94% overall sample purity is very comparable to the purities seen in narrowband surveys at similar redshifts, e.g., 95% for Hα at z = 0.84 (Sobral et al 2013), 93.7% for Hα at z = 0.47, and 90.4% for [OIII] at z = 0.93 (Khostovan et al 2020). We summarize our spectroscopically confirmed HAEs and O3Es in Table 1.…”
Section: Spectroscopic Redshiftssupporting
confidence: 70%
See 2 more Smart Citations
“…Hereafter, when referring to HAEs or O3Es, we also imply that each species lies in these redshift bounds, and that [OIII] refers to [OIII]λ5007 unless otherwise stated. Our 94% overall sample purity is very comparable to the purities seen in narrowband surveys at similar redshifts, e.g., 95% for Hα at z = 0.84 (Sobral et al 2013), 93.7% for Hα at z = 0.47, and 90.4% for [OIII] at z = 0.93 (Khostovan et al 2020). We summarize our spectroscopically confirmed HAEs and O3Es in Table 1.…”
Section: Spectroscopic Redshiftssupporting
confidence: 70%
“…We construct our [OIII] LFs in much the same way as the Hα LFs, except that we do not include an AGN contamination correction. This allows us to make a more direct comparison with other studies that also lack an AGN correction, such as Khostovan et al (2020). In contrast to the Hα LFs, our COSMOS and HEROES ) ∼ 41.75 erg s −1 .…”
Section: Luminosity Functionsmentioning
confidence: 73%
See 1 more Smart Citation
“…On the other hand, our result seems to agreed with the trend observed in other works and cited in Hayashi et al (2013), where the authors found that [O ii]3727 emitters selected by narrow-band (NB) techniques are likely to be dust-poor systems. For example, both Hayashi et al (2013) and Khostovan et al (2020) give A Hα ∼ 0.35 mag for emitters at z ∼ 1.47, Hayashi et al (2015) found A Hα = 0.63 mag for z = 1.5, and Khostovan et al (2015) obtains A Hα = 0.55 ± 0.12 mag for emitters at z = 1.59. Nevertheless, the large dispersion of the mean value derived makes difficult to obtain a clear conclusion about the absorption nature of our emitters.…”
Section: Extinction Correctionmentioning
confidence: 99%
“…Other works have used the combination of Hβ and [O iii], for example De Barros et al (2019) reaching as far as z ∼ 8; Khostovan et al (2015) up to 0.84 < z < 3.24; and Sobral et al (2015) up to z = 1.4. In addition, there are a series of works were the LF is obtained by employing the doublet [O iii] λλ4959,5007 alone, for example, in Ly et al (2007) at 0.41 < z < 0.84; Bongiovanni et al (2020) at z ∼ 0.83; Khostovan et al (2020) at 0.91 < z < 1.10; or Hayashi et al (2020) at 0.05 < z < 0.94.…”
Section: Introductionmentioning
confidence: 99%